Component Analysis to Design an Integral Sustainability Model for Micro, Small and Medium-Sized Enterprises (LACCEI, 2024)
Micro, small, and medium enterprises (MSMEs) are the engine of economic, environmental and social stability in many countries but recently MSMEs have been facing instability in their sales, production, and feature a decrease in employment that generates negative growth in the gross domestic product in emerging countries. Also, along with governmental entities, they are expected to be aware of the importance of developing sustainable models to improve production systems within the framework of sustainable development. Considering there is abundant literature on multiple sustainable models, their effective implementation in production systems is a debate topic as there is no standard guide to the processes and activities that should be followed in their adoption. The objective of this study is to design an integral sustainability model for MSMEs through the analysis of the interrelationships and dependencies of sustainability factors and a perception analysis evaluating 327 MSMEs in Colombia, using the design science research and case study as a research method. The analysis of the results has been exposed as results of a doctoral thesis which indicates that the MSMEs that were studied presented significant variations and similarities in the use of the adoption of sustainable strategies, which allowed the identification of weaknesses and strengths to focus efforts on the development of productive systems aligned with environmental sustainability